A literature review: mechanisms of antitumor pharmacological action of leonurine alkaloid - Cao, Qiang; Wang, Qi; Wu, Xinyan; Zhang, Qi; Huang, Jinghan; Chen, Yuquan; You, Yanwei; Qiang, Yi; Huang, Xufeng; Qin, Ronggao; Cao, Guangzhu (Frontiers in Pharmacology, 2023)
Leonurine refers to the desiccated aerial portion of a plant in the Labiatae family. The primary bioactive constituent of Leonurine is an alkaloid, Leonurine alkaloid (Leo), renowned for its substantial therapeutic efficacy in the treatment of gynecological disorders, in addition to its broad-spectrum antineoplastic capabilities. Over recent years, the pharmacodynamic mechanisms of Leo have garnered escalating scholarly interest.Leo exhibits its anticancer potential by means of an array of mechanisms, encompassing the inhibition of neoplastic cell proliferation, induction of both apoptosis and autophagy, and the containment of oncogenic cell invasion and migration. The key signal transduction pathways implicated in these processes include the Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL), the Phosphoinositide3-Kinase/Serine/Threonine Protein Kinase (PI3K/AKT), the Signal Transducer and Activator of Transcription 3 (STAT3), and the Mitogen-Activated Protein/Extracellular Signal-Regulated Kinase (MAP/ERK).This paper commences with an exploration of the principal oncogenic cellular behaviors influenced by Leo and the associated signal transduction pathways, thereby scrutinizing the mechanisms of Leo in the antineoplastic sequence of events. The intention is to offer theoretical reinforcement for the elucidation of more profound mechanisms underpinning Leo's anticancer potential and correlating pharmaceutical development.